Publish or perish : the educator«s imperative - Glatthorn, Allan A. 1924- (Corwin Press, Inc, 2002)
Successfully translating thoughts and ideas into the printed word can seem daunting to even the most experienced educator. Step-by-step, author and scholar Allan A. Glatthorn guides education professionals through the basics of the writing process, empowering them with the tools to create and enhance their own professional submissions and writings. The down-to-earth, conversational tone helps to effectively convey and outline specific writing strategies for contributions to research journals, articles, op-ed pieces, manuscripts, literature reviews, theses, funding proposals, internal organizational writing.